1988
DOI: 10.1002/art.1780310406
|View full text |Cite
|
Sign up to set email alerts
|

Two ro (ss‐a) autoantibody responses in systemic lupus erythematosus

Abstract: Sdnuclear RNP were quantitated by enzyme-linked immunosorbent assay in 106 white patients with systemic lupus erythematosus. Two Ro autoantibody subgroups were identified that differed quantitatively, genetically, and clinically. The subgroup having anti-Ro only demonstrated significantly lower mean anti-Ro levels than did the subgroup with concomitant anti-La and showed a strong association with the linked HLA alleles DR2 and DQwl. The anti-Ro with anti-La sub- group was associated with the linked HLA alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(20 citation statements)
references
References 38 publications
1
18
1
Order By: Relevance
“…Previous studies have demonstrated that the presence of the HLA-DR3-DQ2 haplotype is highly associated with a more diversified La/Ro RNP response, whereas the haplotype HLA-DR2-DQ1 is associated with a less diversified La/Ro RNP response (5,(45)(46). Our previous data (47) also confirmed the association of HLA-DR2 or HLA-DR3 with more diversification of hRo60-induced autoantibodies to involve other RNPs including mRo52, mla, and mouse Sm as detected by immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the presence of the HLA-DR3-DQ2 haplotype is highly associated with a more diversified La/Ro RNP response, whereas the haplotype HLA-DR2-DQ1 is associated with a less diversified La/Ro RNP response (5,(45)(46). Our previous data (47) also confirmed the association of HLA-DR2 or HLA-DR3 with more diversification of hRo60-induced autoantibodies to involve other RNPs including mRo52, mla, and mouse Sm as detected by immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…HLA class II phenotype might support epitope spreading. The presence of anti-Ro and/or anti-La antibodies is more strikingly associated with HLA-DR3 and/or HLA-DR2 [103, 104]. HLA-DR3 is associated with both anti-Ro and anti-La antibody production while HLA-DR2 favors anti-SSA antibody synthesis [105].…”
Section: Anti-ro Antibody and Demographic Featurementioning
confidence: 99%
“…Initial studies s u g g e s t e d that S S -A (also k n o w n as " R o " ) antigen was a single 6 0 -k D a p r o t e i n ; s u b s e q u e n t reports d e m o n s t r a t e d p r o t e i n s r e a c t i v e w i t h a n t i -S S -A antibody including a 5 2 -k D a p r o t e i n in all n u c l e a t e d cells [3] and a 5 4 -k D a p r o t e i n in non-nucleated red blood cells [21,22,31]. Anti-SS-A antibody also is found in low titers in normal adults [ 18] and ina subset of patients with multiple myeloma [361.…”
Section: Autoantibodies and Autoantigens In Ssmentioning
confidence: 99%